NARASI BEREKSPRESI: CREATING A SPACE FOR SELF-EXPRESSION THROUGH ROLE-PLAYING AT MUAWANAH ORPHANAGE, SEMARANG: NARASI BEREKSPRESI: MENCIPTAKAN RUANG EKSPRESI DIRI MELALUI BERMAIN PERAN DI PANTI ASUHAN MUAWANAH SEMARANG - Raihan Adib Ghifari (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Muawanah Orphanage in Semarang has a diverse population. However, these orphanages still face limited facilities that support self-expression and children's psychological development, especially in emotional expression and social interaction. Objective: This community service program aims to provide a space for children to express themselves through role-playing as a medium for language training, positive emotional expression, and enhanced self-confidence. Method: The Activity was carried out in three stages. First, the preparation stage includes observation and the implementation of a pretest using a questionnaire. Second, the implementation stage is carried out through role-playing-based drama activities, including script introductions, role divisions, exercises, and drama staging. Third, the evaluation stage is conducted using pre- and post-tests administered via a Likert-scale questionnaire to measure children's participation, involvement, and readiness in expressive activities. Results: Children's participation in drama activities, group cooperation, and readiness to perform in public increased. Observations during practice and staging showed increased expressive interaction and engagement among children. Conclusion: The Program Narasi Berekspresi helps provide a safe and positive space for children to practice expression and social interaction through art-based drama-staging activities.